Spreading Of Avian Flu On Duck And Its Impact On Social Economy: Lesson Learnt From Avian Flu Cases On Chicken - Nyak Ilham (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2013)
Bird flu disease that attacks duck dismissed the notion of duck immune to bird flu disease. Learning from the experience ofbird flu disease that attacks poultry in the year of 2004-2005, necessary to measure the spread of disease prevention bird flu in ducks. This paper aims to describe the business and trade patterns of duck associated with the spread of avian influenza and predict the socio-economic impact of bird flu on duck farms in Indonesia. Duck rearing patterns mostly are in the extensive and semi-intensive system, that have large potential disease transmission occured between duck and wild. Illegal trade in the crossborder region and imports from countries that re-export it, ias alo become potential as well as the entry point to the bird flu virus in Indonesia. Ducks trade between regions by land transportation is difficult to control as well becomes the potential media to spread of the virus to a wider area. The economic impact of bird flu on duck business occured due to the death of ducks, decline in production and loss of job opportunities, while that on demand reduction was not significant. Small scale farmers that were bankrupt as a result of bird flu outbreaks may require technical assistance and access to capital for recovery. In the future, development of ducks business should be directed at duck farms into a semi-intensive and intensive system to facilitate the control of epidemic diseases.Key words: Bird flu, ducks, impact, social economic